Poučavanje imeničke sklonidbe u nastavi hrvatskoga kao stranoga jezika - Cvikić, Lidija (Array, 2003)
In the last few years the interest for learning Croatian as foreign language has increased. The teaching methods depend on different types of schools (courses), the number and the profile of students, and they also depend on language system. In this paper we will show some of the existing (and possible) methods in teaching Croatian as foreign language. We will put the accent on the issues and difficulties in teaching Croatian noun declination regarding number, gender and case order.